2021
DOI: 10.1183/23120541.00950-2020
|View full text |Cite
|
Sign up to set email alerts
|

INTREPID: single- versus multiple-inhaler triple therapy for COPD in usual clinical practice

Abstract: IntroductionReal-world trial data comparing single- with multiple-inhaler triple therapy (MITT) in COPD patients are currently lacking. The effectiveness of once-daily single-inhaler fluticasone furoate (FF)/umeclidinium (UMEC)/vilanterol (VI) and MITT were compared in usual clinical care.MethodsINTREPID was a multicentre, randomised, open-label, phase IV effectiveness study comparing FF/UMEC/VI 100/62.5/25 µg via the ELLIPTA inhaler with a clinician's choice of any approved non-ELLIPTA MITT in usual COPD clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
2
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(54 citation statements)
references
References 29 publications
1
48
2
3
Order By: Relevance
“… 9 , 10 In addition, the INTREPID study recently demonstrated that patients treated with FF/UMEC/VI had a higher likelihood of achieving a clinically relevant improvement in health status, as assessed by the COPD Assessment Test, than those treated with MITT. 11 …”
Section: Introductionmentioning
confidence: 99%
“… 9 , 10 In addition, the INTREPID study recently demonstrated that patients treated with FF/UMEC/VI had a higher likelihood of achieving a clinically relevant improvement in health status, as assessed by the COPD Assessment Test, than those treated with MITT. 11 …”
Section: Introductionmentioning
confidence: 99%
“…[30][31][32][33][34][35][36][37] In particular, significantly more patients in the INTREPID trial who were treated with FF/UMEC/VI achieved health status improvement compared to those receiving non-ELLIPTA MITT. 38 These improvements could be attributed to improved adherence with SITT, and a resultant lack of missed doses that is associated with the use of multiple inhalers. Patients with moderate to severe COPD who require triple therapy may therefore benefit from switching to SITT, which has the potential to improve both https://doi.org/10.2147/COPD.S336158…”
Section: Healthcare Utilizationmentioning
confidence: 99%
“…International Journal of Chronic Obstructive Pulmonary Disease 2022:17 422 adherence and outcomes. [38][39][40] Indeed, in a recent study carried out in the USA, patients with COPD initiating FF/UMEC/VI were found to have better adherence than those initiating MITT. 14 A recent study using an economic model estimated that increased use of SITT in patients with moderate to severe COPD would be associated with improved adherence, decreased exacerbation and mortality rates, and healthcare cost savings.…”
Section: Dovepressmentioning
confidence: 99%
“…In another work by K endall et al [ 41 ] using data from the INTREPID trial [ 42 ] and UK cost data, single-inhaler triple therapy with fluticasone, umeclidinium and vilanterol was found to be cost-effective and cost-saving in several estimated scenarios compared to non-Ellipta multiple-inhaler triple therapy.…”
Section: Group 103: General Practice and Primary Carementioning
confidence: 99%